Cytogenetic studies of F1 Hybrid Capsicum annuum L. x Capsicum chacoense (Hunz). - C. Panda, Sape Subba Tata, K.G. Raja Rao, Owk Aniel Kumar, Ramesh. (Journal of Phytology, 2010)
Interspecific F1 hybrid between Capsicum annuum var. cerasiformis (cultivated) and Capsicum chacoense Hunz. (wild) was obtained. The F1 hybrid resembled C. chacoense parent more in gross morphological features such as growth habit, leaf structure and position, shape and size of the fruit. The mean chiasma frequency in the F1 hybrid was less compared to either of the parents indicating reduced homologies between the parental taxa. The meiotic studies further revealed that the two parents involved in the cross differed from each other by two translocations, an inversion and some minor structural alterations. The hybrid was weak and highly sterile (pollen and seed). Isolating mechanisms such as hybrid weakness and hybrid sterile on operative among the parental taxa.